Optimizing injection time of GFP plasmid into sheep zygote. Issue 3 (9th January 2021) - Ebrahimi, Mohammadreza; Mara, Laura; Chessa, Bernardo; Chessa, Fabrizio; Parham, Abbas; Dattena, Maria
Abstract: Microinjection of exogenous DNA into the cytoplasm of matured oocytes or zygotes is a promising technique to generate transgenic animals. However, the data about the microinjection time and procedure in sheep are limited and have not treated in detail. To obtain more in‐depth information, the Sarda sheep oocytes from abattoir‐derived ovaries were subjected to IVM and IVF. Then, the GFP plasmid as a reporter gene was injected into the cytoplasm of MII oocytes ( n : 95) and zygotes at different post‐insemination intervals (6–8 hpi, n : 120; 8–10 hpi, n : 122; 10–12 hpi, n : 110 and 12–14 hpi, n : 96). There were no significant differences in the cleavage rates between the groups. However, blastocyst rate of injected zygotes at all‐time intervals was significantly lower than injected MII oocytes and control group ( p  < 0.05). Interestingly, the proportion of GFP‐positive embryos was higher at 8–10 hpi compared with other injected groups (4 % versus 0 %, p   < 0.01). Among these, the proportion of mosaic embryos was high and two of those embryos developed to the blastocyst stage. In conclusion, we settled on the cytoplasmic microinjection of GFP plasmid at 8–10 hpi as an optimized time point for the production of transgenic sheep and subsequent experiments. Abstract : Steps in experiment 1 and 2. hpf: hours post fertilization.